Isolation of Salmonella sp. from Eggs Commonly Sold in Tondano Market, Minahasa, North Sulawesi - Britney Meissy Pandoh; Herry Maurits Sumampouw; Helen Joan Lawalata; Danny Christian Posumah; Anita Constanci Christine Tengker; Yermia Semuel Mokosuli (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
Various types of eggs are one of the foodstuffs that are in great demand by the community, especially the people of North Sulawesi, because they are cheap and easy to obtain. Furthermore, eggs have the nutritional content of animal protein, which is good for humans. Numerous studies on eggs have revealed that microorganisms, including Salmonella sp., can contaminate them. This study aims to detect Salmonella sp. bacteria in various types of eggs in the Tondano Market, Minahasa, North Sulawesi. This research uses a descriptive method (qualitative method) to describe an event objectively. We collected up to three samples, the first of which is located outside the market. Three samples of purebred chicken eggs, duck eggs, and quail eggs were taken. Then, the second point inside the market was taken: 3 samples of purebred chicken eggs, duck eggs, and quail eggs from the same trader. To prepare the samples, the eggshells were separated from the insides, then 2 grams of the eggshells were crushed and mixed with 5 ml of Buffered Peptone Water (BPW) 0.1%. This mixture was then added to 10 ml of Rappaport Vassiliadis (RV) media, followed by scraping onto Salmonella Shigella Agar (SSA) media, and then inoculating onto Xylose Lysine Deoxycholate agar (XLD) media. Four eggshell samples tested positive for Salmonella sp. bacteria: duck eggs (TB 1), quail eggs (TP 1), broiler eggs (TA 2), and quail eggs (TP 2), while two samples were negative: broiler eggs (TA 1) and duck eggs (TB 2). In contrast, two samples were negative for Salmonella sp., namely broiler eggs (TA 1) and duck eggs (TB 2).